(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to 1) study and compare the leadership styles for Thailand 4.0 among school administrators classified by school status and size within the jurisdiction of Bangkok 2) study and compare operations in the educational quality assurance system of secondary schools within the jurisdiction of Bangkok under the new educational quality assurance framework classified by school status and size and 3) study the predictive power of the leadership style for Thailand 4.0 of school administrators impacting the implementation of the education quality assurance system under the new education quality assurance framework, classified by school status and size within the jurisdiction of Bangkok affecting the implementation of the educational quality assurance system of schools within the jurisdiction of Bangkok. The sample was 201 school administrators and teachers. The research instruments were questionnaires. The research found that the leadership style for Thailand 4.0 within the jurisdiction of Bangkok of school administrators was at high level. The comparative results classified by overall status showed that there was a statistically significant difference in style at .01 levels. When compared from the overall school size classification within the jurisdiction of Bangkok, there was a statistically significant difference in style at the .05 level (2). The implementation of the educational quality assurance system at secondary schools within the jurisdiction of Bangkok under the new educational quality assurance framework was at high level. The comparative results classified by overall status showed that there was a statistically significant difference in style at .01 levels. When compared by size of schools within the jurisdiction of Bangkok, there was a statistically significant difference at .05 levels (3). The results of a predictive power analysis of leadership style for Thailand 4.0 among school administrators found that there were five components capable of forecasting operations in the education quality assurance system under the new framework for quality assurance for secondary schools within the jurisdiction of Bangkok under the new educational quality assurance framework, at 89% considere